PERLINDUNGAN PEKERJA MIGRAN ILEGAL INDONESIA KORBAN PERDAGANGAN ORANG DI MALAYSIA MENURUT PROTOKOL PALERMO TAHUN 2000: Protection of Indonesian Illegal Migrant Workers Victims of Trafficking in Malaysia According to the Palermo Protocol of 2000 - Aura Ratrika; Jun Justinar (Reformasi Hukum Trisakti, 2024)
Human trafficking has been a crime that has existed for a long time. In the present era, human trafficking in Indonesia involves illegal migrant workers moving to other countries without proper documentation. The Indonesian government has ratified the Palermo Protocol as a commitment to combat human trafficking. The issues addressed in this research are the obligations of Indonesia as a signatory to the Palermo Protocol of 2000 and the efforts made by the Indonesian government to prevent and protect Indonesian migrant workers who become victims of human trafficking in Malaysia. This study is a normative research using secondary data. The data is analyzed qualitatively and concluded using deductive methods. Based on the research findings and analysis, it is evident that Indonesia's obligations as a signatory to the Palermo Protocol of 2000 include taking legislative. The Indonesian government protects Indonesian migrant workers who are victims of human trafficking by keeping the victims' identities confidential, providing restitution to the victims, rehabilitating them, offering legal assistance, ensuring social reintegration, and assisting in the repatriation of victims. The conclusion is Indonesia has fulfilled the obligations ordered the 2000 Palermo Protocol by making a number of efforts to prevent and protect illegal Indonesian migrant workers.